Auroral emissions and inner magnetospheric dynamics during Earth's response to the 28th October 2021 Coronal Mass Ejection - Waters, J. E.; Jackman, C. M.; Whiter, D. K.; Fogg, A. R.; Lamy, L.; Carter, J. A.; Coxon, J. C.; Fryer, L.; Louis, C. K.; Paxton, L. J.; Briand, C.; Cecconi, B.; et al. (Dublin Institute for Advanced Studies, 2023)
On 28th October 2021 the Sun released a large Coronal Mass Ejection (CME) in Earth's direction. An X1.0 class solar flare and a rare ground level enhancement (GLE) were observed, along with bright solar radio bursts. Here we examine data from the near-Earth environment to investigate the terrestrial response to this solar event, using newly accessible Wind Auroral Kilometric Radiation (AKR) observations. The CME arrival is tracked at ~1 AU using remote radio observations from Wind, along with in-situ interplanetary magnetic field (IMF) and solar wind measurements from OMNI. Geomagnetic activity is studied with SYM-H, SuperMAG and PC indices. The auroral response is monitored for the first time with Wind AKR observations from L1 (Lagrange point 1), UV auroral emissions and field-aligned current densities, exploring the AKR source location and inner magnetospheric dynamics. We thus quantify the timeline for solar wind—magnetosphere—ionosphere coupling and address the visibility of AKR sources from Wind's position on the dayside at L1.